2006
DOI: 10.1038/sj.ijo.0803252
|View full text |Cite
|
Sign up to set email alerts
|

Intra-abdominal adipose tissue deposition and parity

Abstract: Objective: To determine the relationship between body composition/fat distribution and parity after adjusting for potential confounders: age, smoking, and physical activity. Design: Cross-sectional. Subjects: A total of 170 Caucasian women between the ages of 18 and 76 years, who were non-smokers with no cardiovascular disease, diabetes, metabolic, or endocrine disorders. Measurements: Physical activity assessment (Baecke Physical Activity Questionnaire), anthropometric measures, and body composition (dual-ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 29 publications
4
41
0
6
Order By: Relevance
“…It is suggested that after pregnancy, there is a preference for fat accumulation in the visceral adipose tissue [40]. Similarly, in a sample of 170 American women aged 18-76 years, it has been found that the intra-abdominal fat tissue increased as the number of parturitions increased, regardless of age, body fat percentage, physical activity, and smoking [41].…”
Section: Prevalence Of Abdominal Obesitymentioning
confidence: 97%
“…It is suggested that after pregnancy, there is a preference for fat accumulation in the visceral adipose tissue [40]. Similarly, in a sample of 170 American women aged 18-76 years, it has been found that the intra-abdominal fat tissue increased as the number of parturitions increased, regardless of age, body fat percentage, physical activity, and smoking [41].…”
Section: Prevalence Of Abdominal Obesitymentioning
confidence: 97%
“…It is interesting to note in this context that an association of parity and visceral fat mass has been demonstrated recently. 35 In our study, serum AFABP levels are positively associated with IMT in both genders. However, this association is lost in multivariate analysis adjusting for markers of obesity and renal function.…”
Section: Discussionmentioning
confidence: 63%
“…32 Previous studies suggest that weight gained in pregnancy and retained after pregnancy includes fat as opposed to lean mass. [33][34][35][36] We did not find a direct association between cumulative pregnancy weight gain and hepatic steatosis, or number of pregnancies and hepatic steatosis, because pregnancy may not lead to significant accumulations of fat in the liver, even as it leads to increased fat mass and visceral fat deposition. Alternatively, it is possible that the associations between pregnancy and increases in hepatic steatosis during the reproductive years are attenuated as women age; in Michigan SWAN, hepatic steatosis was ascertained approximately 8 years after the menopausal transition.…”
Section: Discussionmentioning
confidence: 67%